2015
DOI: 10.1111/neup.12191
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative changes in patients with clinical history of bipolar disorders

Abstract: Neurodegeneration in bipolar disorder (BPD) is poorly understood. Therefore, the current study was designed to assess the immunohistochemical changes in neurodegenerative markers in patients with BPD. Eleven consecutive autopsy cases diagnosed with BPD were analyzed. Sections were obtained from archival paraffin blocks of representative areas and stained using conventional methods, as well as immunostained with several antibodies to screen for neurodegenerative diseases. Age-and nonargyrophilic grains (AGs) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…In Japan, overdiagnosis of BD, which is accelerated by the premature approval of near‐infrared spectroscopy as a diagnostic tool, is discouraged . The boundary between genuine BD and secondary BD can be obscured, as evidenced by a recent neuropathological study of post‐mortem brains from aged BD patients that showed a high frequency of tau pathology in emotion‐related brain areas . Soon, PET might be used for the distinction between genuine BD and secondary BD .…”
Section: Diagnosismentioning
confidence: 99%
“…In Japan, overdiagnosis of BD, which is accelerated by the premature approval of near‐infrared spectroscopy as a diagnostic tool, is discouraged . The boundary between genuine BD and secondary BD can be obscured, as evidenced by a recent neuropathological study of post‐mortem brains from aged BD patients that showed a high frequency of tau pathology in emotion‐related brain areas . Soon, PET might be used for the distinction between genuine BD and secondary BD .…”
Section: Diagnosismentioning
confidence: 99%
“…The first reported clinical feature in AGD cases is dementia . Subsequently, it was also reported that AGD may be associated with several psychiatric conditions in late life . Pathologically, it is known that AGD often coexists with other neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 Subsequently, it was also reported that AGD may be associated with several psychiatric conditions in late life. [2][3][4] Pathologically, it is known that AGD often coexists with other neurodegenerative diseases. However, whether the comorbidity reflects some pathogenic linkage and affects clinical presentations in other diseases remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This was for a while mainly seen in the context of neurotransmitter availability in relevant brain structures and, according to this context, actions of antidepressants were interpreted and developed. The suspicion that neurodegeneration may play a crucial role is not entirely new, but has gained increasing attention mainly during the last years [1][2][3][4][5][6] . In the beginning, this seemed more likely in cases in which patients exhibited socially unacceptable behavior or signs of dementia, [7][8][9][10] but was less considered in exclusively depressive disorders, a view that is actually changing 2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The suspicion that neurodegeneration may play a crucial role is not entirely new, but has gained increasing attention mainly during the last years [1][2][3][4][5][6] . In the beginning, this seemed more likely in cases in which patients exhibited socially unacceptable behavior or signs of dementia, [7][8][9][10] but was less considered in exclusively depressive disorders, a view that is actually changing 2,4 . On the one hand, reduced neurotransmitter concentrations in the synaptic cleft may already be associated with the initiation of neurodegenerative processes, as judged from the influence of other synaptopathic changes, 10,11 and from the fact that classic antidepressants can also display neuroprotective properties 12 .…”
Section: Introductionmentioning
confidence: 99%